Personnel problems in the Russian engineering industry: a review and analysis of structural reasons ("Journal "U". Economy. Management. Finance.", 2025)
This article examines the personnel problems in the Russian engineering industry and provides an overview and analysis of the structural causes of the shortage of labor resources. Based on data from Rosstat, the Higher School of Economics, and sectoral studies, it examines key trends: structural shifts in employment influenced by defense orders, growing staff shortages, wage dynamics, and the imbalance between supply and demand in the labor market. The aim of this review is to identify the main trends and challenges in employment within the machine‑building complex.
Keywords: mechanical engineering; labor resources; workforce shortage; skills mismatch; education-industry integration